HIV knowledge and protective factors among racial-ethnic minority youth: moderation by ethnic identity and LGBQ+ identity - Lardier, David T.; Opara, Ijeoma; Ngozi Asabor, Emmanuella; Bell, Felicity; Garcia-Reid, Pauline; Reid, Robert J. (Journal of LGBT youth, 2024)
Due to systemic racism and homophobia, Lesbian, Gay, Bisexual, and Queer (LGBQ+) youth of color are disproportionately affected by HIV (human immunodeficiency virus)/AIDS (acquired immunodeficiency syndrome) and viral hepatitis (VH). Innovative approaches that acknowledge strengths such as ethnic identity need to be examined to understand specific protective factors that can support LGBQ + youth of color. This study aimed to examine the moderating effects of ethnic identity and LGBQ + identity on indicators of HIV knowledge (i.e., VH knowledge, sexual negotiation skills, and perception of sexual risk). Youth who identified as Hispanic/Latinx, African American/Black, and mixed racial-identity (N = 564) were included in the delimited sample. Using linear regression modeling, results showed that there was a positive association between sexual negotiation skill, sexual risk perception, ethnic identity and HIV knowledge. Ethnic identity displayed a positive and significant moderating effect between predictors and HIV knowledge. Three-way interactions between predictors by ethnic identity × LGBQ + interaction showed equally interesting associations with HIV knowledge. Study implications include the need for strengthening ethnic identity and pride among LGBQ + youth of color within HIV prevention programming.